(untitled) (Journal of the College of Basic Education, 2026)
Biographies are a science characterized by precision, based on sources and references that address the lives of well-known individuals who played a significant role in history. Scholars write biographies based on their beliefs, work, location, affiliation, or nationality. These biographies may be long or short, in-depth or superficial, depending on the circumstances of the era in which the biography was written, the culture of the translator, and their ability to draw a clear, complete, and accurate picture from the sum of the knowledge and information they have gathered about the person being translated . Through this study, which clarifies the methodology of Ibn Abd al-Barr al-Qurtubi in the field of biographies, who had the lion’s share in this field, he authored important works of scholarly weight and historical value. He wrote biographies of the Companions and other prominent figures in the scholarly community, some of which have reached us, while others, unfortunately, have not reached us. Some are considered lost, while others have been printed, the most famous of which are (Al-Isti’ab), Al-Intiqad, and Al-Inbah. Then there are the remaining works, which will be mentioned later in the research.